The Role of Input Litter Quality and Quantity on Soil Organic Matter Formation and Sequestration in Rehabilitated Mine Soil - Singh, Preeti; Ghosh, A.K.; Kumar, Santosh (Indian Forester, 2022)
Several anthropogenic factors including mining cause land degradation. The negative impacts of coal mining in accentuating the greenhouse effect may include carbon dioxide (CO2) emission from fell biomass and mineralization of soil organic matter (SOM) exposed by land disturbance. SOM content declines drastically in soils disturbed by mining. Thus soil restoration and reestablishment of vegetation cover on disturbed land could lead to carbon (C) sequestration. The present paper reviewed the research on carbon sequestration related to litter substrate quality and quantity, including litter decomposition, litter nutrients release and molecular property of C sequestered. The present paper aimed to clarify the relationship between soil organic matter formation, litterfall, and litter quality, which will help to understand forest succession in restored mine soil and soil organic matter formation.